Metal‐Free C–S Bond Cleavage to Access N‐Substituted Acrylamide and β‐Aminopropanamide. Issue 33 (26th August 2019) - Yang, Ke; Li, Yi; Ma, Zhiyan; Tang, Long; Yin, Yue; Zhang, Hao; Li, Zhengyi; Sun, Xiaoqiang
Abstract : Metal‐free and Selectfluor‐mediated C–S bond cleavage is described. This novel strategy provides a facile and efficient method to access important N ‐substituted acrylamide and β‐aminopropanamide derivatives with good functional group tolerance and yields. Abstract : The metal‐free C–S bond cleavage process has been established to construct N ‐substituted acrylamide and β‐aminopropanamide derivatives in the presence of Selectfluor.